Legal Consequences of an Heir’s Delay in Accepting Inheritance under Civil Law - Majid, Ridhwan Ardra; Herwastoeti; Indri Hapsari, Dwi Ratna (Jurnal Cakrawala Hukum, 2025)
The purpose of this research is to find out how the impact of the Consequences of a Delay in Receiving an Inheritance is reviewed in terms of Civil Inheritance Law, which is what if an heir can be said to have lost his right to get an inheritance or inheritance and to find out the consequences of the delay of an heir to know and obtain or receive an inheritance from the heir. The research method used in this writing uses a normative method with a legal approach and can find the conclusion that the loss of the right of the heir to receive the inheritance is also caused by the impropriety where the impropriety is that the heir kills, harms, or tries to harm the heir, the heir slanders the heir, the heir tries to harm the heir to revoke his will, the heir embezzles, damages, and forges the will of the heir, and the heir rejects an inheritance and the expiration date of an heir to exercise his right to receive the heir is within 30 (thirty) years from the date of disclosure of the inheritance which is not entirely the right of the heir.